ISLAMIC EDUCATION: OPPORTUNITIES AND CHALLENGES IN SECULAR PHILIPPINE STATE - Sahraman Dimakuta Hadji Latif (SAINTEKBU, 2013)
Philippines is  a secular state which mandates by its constitution the observation of separation of church and state. Religious freedom and tolerance are ensured within this secular principle; and Filipino can enrich themselves with Islamic knowledge and values, and reinforce their Islamic education. Along this secular state, the roles of Madrasah education have played vital contribution for the spread of Islam and Islamic moral values enhancements of the Filipino Muslims. There are auspicious opportunities for Muslims under this secular government in respect and recognition of their beliefs, customs, traditions and religion. Among those indubitable opportunities are the creation of Muslim autonomy known as Autonomous Region In Muslim Mindanao which still under the framework of the Philippines constitution,  the  implementation of sizeable portion of the Shariah Law known as Code of Muslim Personal Laws of the Philippines ,  the creation of National Commission on Muslim Filipinos which is aimed to serve the needs of the Muslim minorities , and the establishment of Mindanao State University for cultural integration of the people of Mindanao. Unfortunately, along these great opportunities, Islamic education in the Philippines is still under the zenith of deterioration and backwardness. Islamic institutions only  serve  to strengthen the moral and spiritual needs of the Filipino Muslims. It does not produce quality and competitive graduates embraced with compounding skills and earthly knowledge who are capable of facing the challenge of globalization and national employment demand. Hence, this study is conducted to provide  compounding inputs for local Muslim leaders, ulama and madrasah institutions to come up necessary policies and remedies for the present declining Islamic education in the Philippines. It discusses the opportunities and challenges of Islamic Education in the Philippines in general. Qualitative research method is used; and data are gathered from relevant studies, works and personal interviews.This research concludes that Islamic education in the Philippines has been remained stagnant and backward. Opportunities given to Muslims under this secular state are not utilized optimally for Islamic education advancement.  Keywords: Islamic education, secular state , Philippines, opportunities , challenges,  minority Muslims.